Dendritic cells pulsed with prostate-specific membrane antigen in metastatic castration-resistant prostate cancer patients: a systematic review and meta-analysis - Mohammad Mohammadzadeh; Masoud Shirmohammadi; Morteza Ghojazadeh; Leila Nikniaz; Mortaza Raeisi; Seyed Ali Mousavi Aghdas (Prostate International, 2018)
Background: Dendritic cells (DCs) are used in many malignancies as vaccines to induce immunity against specific cancer antigens. The role of DCs in metastatic castration-resistant prostate cancer (mCRPC) is not determined. In this study, the proportion of mCRPC patients with clinically significant response to targeted therapy by DCs pulsed with prostate-specific membrane antigen was evaluated, and the possible adverse effects of this modality were investigated. Methods: Major databases were searched up to Feb 2017, to identify studies in which the antitumor efficacy of DCs pulsed with the extracellular portion of PSMA was studied for the treatment of mCRPC. Data were collected by two reviewers and analyzed using Comprehensive Meta-Analysis software, version 2.0. Findings: Our study consisted of 6 nonrandomized prospective (cohort) trials, overall reporting on 153 mCRPC patients. The event rate that is the representative of fraction of patients showing antitumor response was 0.43 (95% confidence interval = 0.355–0.512; P = 0.097). No significant between-study heterogeneity or inconsistency was detected (I2 = 5.47; Q = 5; P = 0.382). Our study failed to demonstrate a significant therapeutic efficacy for DCs in mCRPC. However, no significant adverse effects were seen. Keywords: Dendritic cells, Meta-analysis, Metastatic castration resistant, Prostate cancer, Prostate-specific membrane antigen